Effect of Surgeon Age on Bariatric Surgery Outcomes. Issue 5 (May 2018) - Stevens, Haley; Carlin, Arthur M.; Ross, Rachel; Stricklen, Amanda; Wood, Michael H.; Ghaferi, Amir A.
Abstract : Objective: This study sought to explore the relationship of bariatric surgeon age and patient outcomes. Background: Regulators, policy makers, and patient advocacy groups have recently been pushing to establish clear guidelines for physician retirement in the United States. Although it is often assumed that increasing physician age leads to worse patient outcomes, the relationship is lacking robust evidence, and is still unclear. Methods: We conducted a study analyzing all bariatric surgeons in Michigan who participated in a statewide collaborative quality improvement program (n = 71) who performed primary laparoscopic Roux-en-Y Gastric Bypass, or sleeve gastrectomy operations, and data on their patients (n = 60430) over the past 10 years. Our primary outcomes were 30-day postoperative complications. Odds ratios for overall complications and serious complications were calculated for each age group, and surgery type. Results: Late career surgeons had more bariatric surgery experience and had a higher average annual case volume than early career surgeons. Considering all cases in the past 10 years, older surgeons performed more Roux-en-Y Gastric Bypass (40%) and less sleeve gastrectomy (38.8%) than younger surgeons (34.7% and 51.5%). When adjusting for patient and surgeon characteristics, there were no statistically significant differences in overall or serious complication rates for either procedure among surgeon age groups. Conclusions: When evaluating bariatric surgeons in the State of Michigan, we found no statistically significant association between surgeon age and patient outcomes. Our findings do not provide evidence for age-specific retirement cut-offs, but support the development of guidelines which are holistic, and focus on evaluating and improving physician outcomes at all career levels.